JOB SPECIFICATION DALAM PERSPEKTIF MANAJEMEN SUMBER DAYA MANUSIA DAN DALAM PERSPEKTIF ISLAM - Malihah, Lola; Al Hanif, Budiman; Amelia, Zaida; Hayati, Siti NurSa’da; Najati, Afrida (Journal MISSY (Management and Business Strategy), 2022)
This research aims to examine the application of work specialization in human resource management reviews and in islamic perspectives. This research uses a qualitative approach, by reviewing various related theories obtained through literature studies. In the effective and efficient management of human resources, the specificization of work is very important. Job specialization aims to place employees in positions that are in accordance with expertise or competence. The specificity of the work begins with the anlisis of the position and the design of the work before the recruitment and selection process is carried out. In Islam, the specificization of work turns out to be in line with the concept of human resource management, where Islam also teaches that a job must be handed over to people who are in accordance with their skills or competencies.